Discovery, discernment, and exploitation: Entrepreneurial mechanisms at the nexus of individual and opportunity - Barach, Moshe A.; Rider, Christopher I. (Strategic Management Journal, 2023)
Abstract Research Summary Extending the opportunity‐discovery perspective on Kirznerian entrepreneurship, we propose a general framework in which new businesses emerge from three distinct mechanisms situated at the individual‐opportunity nexus: discovery , discernment , and exploitation . We propose observing opportunities in market exchanges and characterizing their profitability potential based on a component that is common to all observers and one that is specific to individual observers who vary in access to market information. Analysis of an online platform for freelance labor demonstrates our contributions in theory, measurement, and inference. In this context, discovery and exploitation mechanisms shape individuals' entrepreneurial transitions from freelancer to founder. We discuss applications of our framework across settings, extensions to other types of entrepreneurship, and the viability of opportunity as an orienting construct for entrepreneurship research. Managerial Summary Entrepreneurial opportunities are present in all markets but there is no systematic way of observing or valuing such opportunities, much less predicting where and when they become the basis for new businesses. We propose doing this with data commonly collected and archived by online platforms. We acknowledge that new businesses are often founded if one is in the right place at the right time; if one can distinguish a great opportunity from a good (or bad) one; or if one is capable of making a market. Our framework makes each of these intuitions empirically distinct, thus offering insights on where, when, and by whom new businesses are likely to be founded.